Relationship between Self-efficacy and Attitudes towards Interprofessional Collaboration and Communication in Learners of Different Disciplines of Medical Sciences - Fatemeh Keshmiri (Kerman University of Medical Sciences, 2021)
Background: Interprofessional collaboration is defined as a key component of a successful team in healthcare system. Interprofessional collaboration facilitates healthcare team members to provide the effective and safe healthcare services.Objectives: This study aimed at investigating the relationship between self-efficacy and attitudes toward interprofessional communication and collaboration in learners of different disciplines.Methods: This cross-sectional study carried out in Shahid Sadoughi University of Medical Sciences in 2020. In the first phase, the psychometrics properties of the scales; attitudes toward healthcare teams and self-efficacy in interprofessional collaboration and communication were evaluated. In the second phase, the survey were conducted among 178 residents, medical interns, and nursing students.Results: The validity and reliability of the instruments were confirmed. According to exploratory factor analysis, the items of the self-efficacy in interprofessional collaboration and communication scale were classified into four areas; effective communication with the patient, patient involvement, interprofessional teamwork, and interprofessional interaction. The Cronbach's alpha coefficient was 0.74 and 0.95, and interclass correlation coefficient was 0.76 and 0.90 for attitudes toward healthcare teams and self-efficacy in interprofessional collaboration and communication scales, respectively. The mean scores of self-efficacies (2.10±0.41) and attitudes toward health care teams (2.17 ±0.43) were at a weak level, and a significant relationship was observed between them (P=0.001, r = 0.80).Conclusion: Regards the confirmation of validation of the tools, the validated instruments can be utilized for formative evaluation of learners in different fields in order to provide the necessary platform for the promotion of interprofessional collaboration behavior in clinical teams.